EFFECT OF SIMULATED TRANSPORTATION ON PHYSICOCHEMICAL PROPERTIES OF BER CV. UMRAN - PREETI; BHANUKAR, MANOJ; GOYAL, R. K. (The Bioscan, 2016)
The work was undertaken to evaluate the effect of simulated transportation by providing different levels of vibration and time duration on physico-chemical properties of ber fruits cv. Umran during transportation and storage under ambient storage conditions. The total soluble solids, TSS: acid ratio and organoleptic rating first increased and then decreased with increase in duration of storage. The TSS, TSS: acid ratio and ascorbic acid content decreased with increased intensity and duration of vibration. The acidity of the fruits first decreased and then increased with increase in period of storage. Based upon above parameters among various levels of simulation vibration and duration of vibration, fruits without simulation vibration were best in maintaining their physico-chemical attributes whereas the simulation vibration given to the fruits up to 50 rpm for 3 and 6 hours were found effective for maintaining their organoleptic acceptability.